Geração de energia elétrica a partir de biogás produzido em estações de tratamento de esgoto - Scheuer, Alex (2019)
Diagnosis of the National Sanitation Information System (SNIS), referring to 2017, indicates that only 46% of the sewage generated is treated. In order to reverse this situation, Brazil committed itself to the United Nations Summit on Sustainable Development by 2030 to “make access to adequate and fair sanitation and hygiene for all”. A study by the National Water Agency (ANA) estimates that it will need R$ 149.5 billion to universalize the collection and treatment of sewage by 2035. Considering that there will be an increase in investment in basic sanitation trying to fulfill the commitments assumed, there is the need to improve the sewage treatment processes adopted, making them more efficient, sustainable and economically practical. It is in this context that the use of biogas can bring great contribution, since the electric energy generated can be used internally in the processes of sewage treatment and exported to the grid. This work investigates the technological routes generating electric energy with the biogas from treating sanitary sewage. Using the electric energy produced, it is expected to lower or cut the use of an external source of electric energy, making the sewage treatment process more sustainable and energy-efficient. From a literature review on the subject, with emphasis on theoretical information and experimental data obtained in other research papers, it was observed that there is a significant improvement in the viability of the projects when the electrical generation is associated with the thermal use of exhaust gases. For energy conversion, the most widely used equipment is internal combustion engines, given their better electrical efficiency, lower acquisition costs and operational simplicity. The main preliminary biogas treatments refer to the removal of moisture and contaminants such as hydrogen sulfide and siloxanes. These treatments have high costs that must be carefully considered in the feasibility studies. The scenario that presented the best feasibility was the application of UASB reactors followed by conventional activated sludge with electric and thermal biogas utilization (cogeneration), with expected return on investments for the benefited populations close to 100,000 inhabitants. The main environmental gains in the biogas energy use refer to the reduction of methane emissions and the reduction of the volume of sludge landfilled through drying in cogeneration arrangements.